Pengaruh NPL dan LDR Terhadap ROA pada Bank BUMN Periode 2014-2021 - Adinda Nurhidayah; Fitriyadi; Irwansyah (Business Administration, FISIP ULM, 2022)
ABSTRACT : This study aims to examine and analyse the Influence of Non Performing Loan (NPL)(X1) and Loan to Deposit Ratio (LDR)(X2) on Return On Assets (ROA)(Y) at Bank BUMN Period 2014-2021. The research methodology employed is a quantitative technique of the explanatory type. The object of this study uses Annual Report Bank BUMN namely PT. Bank Rakyat Indonesia (BRI) Tbk, PT. Bank Mandiri Tbk, PT. Bank Negara Indonesia (BNI) Tbk, PT.Bank Tabungan Negara (BTN) Tbk. This study makes use of secondary data, including financial statements and annual reports released by Bank BUMN for the period 2014-2021. This study's population is comprised of all financial statements and annual reports from Bank BUMN, while the sample is comprised of 32 annual reports from Bank BUMN. This research used purposive sampling. Data analysis methodology employs descriptive staticial analysis, multiple linear regression, the classic assumption test, hypothesis testing, the effective contribution test, and the relative contribution test. The analysis that Bank BUMN did for the years 2014-2021 shows that Non-Performing Loans (NPL) have a 69.6% effect on Return On Assets (ROA). With an influence level of 9, Loan to Deposit Ratio (LDR) shows that it doesn't have much of an effect on Return On Assets (ROA). Return On Assets is affected by Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) together by 78.6%. (ROA). The other 21,4% is affected by factors that this study did not look into.. Keywords: NPL, LDR, ROA